Pendidikan Islam pada Masa Pembaharuan - Mardinal Tarigan; Dinda Afrilia; Nurul Afifah Tanju (Pascasarjana IAI Nasional Laa Roiba Bogor, 2024)
During the time of Prophet Muhammad (peace be upon him), the concept of education was not fully formed as we understand it today. However, through the Prophet's actions and efforts in spreading the teachings of Islam, he served not only as a teacher but also as a character builder. The Prophet's preaching successfully transformed the Arabs in Mecca, who were previously engaged in idol worship, into worshipers of the One God, Allah. Islamic education emphasizes the formation of mental attitudes reflected in tangible actions, both for the benefit of individuals and society. It not only focuses on theoretical aspects but also on the practical implementation of the teachings imparted. Islamic education encompasses the formation of faith and the practice of good deeds simultaneously, as well as aspects of individual and social education. The history of Islamic education has undergone various phases of development alongside the development of Islam itself, from the time of Prophet Muhammad (peace be upon him) to the leadership of the Caliphs in different Islamic states. However, along with the decline of the Muslim community, Islamic education has also experienced a similar decline. This study adopts a Literature Review approach, involving the collection of literature data through digital libraries and the internet, as well as the use of document studies on previous research findings. Journal searches were conducted through Google Scholar and academic literature related to Islamic education during the reform period.